Patient experience of nasal obstruction and its clinical assessment. Issue 4 (7th March 2018) - Nip, L; Tan, M; Whitcroft, K L; Gupta, R; Leung, T S; Andrews, P
Abstract: Background: The correlation between objective and subjective nasal obstruction is poor, and dissatisfaction rates after surgery for nasal obstruction are high. Accordingly, novel assessment techniques may be required. This survey aimed to determine patient experience and preferences for the measurement of nasal obstruction. Method: Prospective survey of rhinology patients. Results: Of 72 questionnaires distributed, 60 were completed (response rate of 83 per cent). Obstruction duration (more than one year) (χ 2 = 13.5, p = 0.00024), but not obstruction severity, affected willingness to spend more time being assessed. Questionnaires (48 per cent) and nasal inspiratory peak flow measurement (53 per cent) are the most commonly used assessment techniques. Forty-nine per cent of participants found their assessment unhelpful in understanding their obstruction. Eighty-two per cent agreed or strongly agreed that a visual and numerical aid would help them understand their blockage. Conclusion: Many patients are dissatisfied with current assessment techniques; a novel device with visual or numerical results may help. Obstruction duration determines willingness to undergo longer assessment.